PRAKTIK TRANSAKSI ONLINE SHOP SISTEM DROPSHIP DALAM PERSPEKTIF HUKUM ISLAM - Lusi Oktaviani (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
The development of information and communication technology is something that can’t be avoided in the current era of globalization, because the development of information and communication technology will run in accordance with the development of science. Information and communication technology causes the world to be borderless and significant social changes take place so quickly. The Internet, the biggest computer network in the world, is currently used by millions of people spread all over the world. Internet users with a variety of activities are already very different from the original purpose of this network. Since business related to the global network system or what is called the internet appeared on the surface, there has been a momentum of change to aspects of people's lives, especially in the field of trade transactions or what is known as e-commerce. Whatever doing by YLX as a supplier of Ayu online shop as a dropshipper who takes advantage of the development of the world of technology by buying and selling via the internet. The collaboration between YLX and Ayu Online shop is very good and does not violate Islamic law as their religion, where YLX provides facilities and trust to Ayu online shop to be her representative in online buying and selling transactions. Ijab and qabul are only carried out via the internet and have fulfilled the pillars and conditions of the wakalah contract. Transactions between the Ayu online shop and the buyer which is a greeting contract are also carried out via the internet. In Islamic law, a salam contract is allowed to carry out a contract using writing (letter) on the condition that the two parties are far apart from each other or the contract actors are silent, for the perfection of the contract it is required that the other person addressed by the writing wants to read the writing. Based on research on the review of Islamic law on online shop dropship systems, it can be concluded that buying and selling and representing something via the internet is allowed, as long as it does not contain elements that can damage it such as riba, tyranny, fraud, cheating and the like and meet the pillars and conditions. In line with this conclusion, it is recommended for online buyers to understand the clarity of item specifications and choose a trusted online shop that presents testimonials, and dropshippers are expected to be open about their status as second hand.